Prosodic Boundaries in Writing: Evidence from a Keystroke Analysis - Fuchs, Susanne; Krivokapić, Jelena (Frontiers in Psychology, 2016)
The aim of the paper is to investigate duration between successive keystrokes during typing in order to examine whether prosodic boundaries are expressed in the process of writing. In particular, we are interested in interkey durations that occur next to punctuation marks (comma and full stops while taking keystrokes between words as a reference), since these punctuation marks are often realized with minor or major prosodic boundaries during reading. A two-part experiment was conducted: first, participants’ keystrokes on a computer keyboard were recorded while writing an email to a close friend (in two conditions: with and without time pressure). Second, participants read the email they just wrote. Interkey durations were compared to pause durations at the same locations during read speech. Results provide evidence of significant differences between interkey durations between words, at commas and at full stops (from shortest to longest). These durations were positively correlated with silent pause durations during reading. A more detailed analysis of interkey durations revealed patterns that can be interpreted with respect to prosodic boundaries in speech production, namely as phrase-final and phrase-initial lengthening occurring at punctuation marks. This work provides initial evidence that prosodic boundaries are reflected in the writing process.